2012
DOI: 10.1177/1932202x12451440
|View full text |Cite
|
Sign up to set email alerts
|

Out of the Mouths of Babes

Abstract: Focus Group interviews with 31 disadvantaged students in an Early College High School (ECHS) program present insights to students' experience in the hybrid school, specifically regarding their perceptions of college readiness. Student "voice" in research can yield significant information when examining aspects of school design that potentially support postsecondary preparation. Three constructs of college readiness were investigated: academic preparedness, social preparedness, and personal preparedness. Themes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…The first research question of this article was quite broad and encompassed both more traditional aspects of early college research (e.g., academic achievement) and the affective and qualitative aspects that have been largely overlooked in previous research (e.g., the actual description of the experience by early college entrants). Aligning with previous positive findings about academic success among early college students (Haxton et al, 2016;Locke & McKenzie, 2016;Locke et al, 2014;McDonald & Farrell, 2012;Ongaga, 2010;Saenz & Combs, 2015;Schumacher et al, 1995), our participants reported positive academic experiences and strong academic performance. Dai et al's (2015) participants seemed to find early college entrance academically challenging with a somewhat difficult transition into a new culture and harder material.…”
Section: Research Question 1: How Do People Who Radically Acceleratedsupporting
confidence: 91%
See 1 more Smart Citation
“…The first research question of this article was quite broad and encompassed both more traditional aspects of early college research (e.g., academic achievement) and the affective and qualitative aspects that have been largely overlooked in previous research (e.g., the actual description of the experience by early college entrants). Aligning with previous positive findings about academic success among early college students (Haxton et al, 2016;Locke & McKenzie, 2016;Locke et al, 2014;McDonald & Farrell, 2012;Ongaga, 2010;Saenz & Combs, 2015;Schumacher et al, 1995), our participants reported positive academic experiences and strong academic performance. Dai et al's (2015) participants seemed to find early college entrance academically challenging with a somewhat difficult transition into a new culture and harder material.…”
Section: Research Question 1: How Do People Who Radically Acceleratedsupporting
confidence: 91%
“…Previous literature reported that early college programs were socially enjoyable or satisfying (Heilbronner et al, 2010;Hertzog & Chung, 2015;Janos et al, 1989;McDonald & Farrell, 2012;Noble et al, 1999;Noble & Smyth, 1995;Ongaga, 2010;Saenz & Combs, 2015;Woodcock & Beal, 2013). Our sample seemed to see it slightly differently, in the sense that participants were more likely to describe it as socially uneventful or average with statements like "It wasn't a disadvantage" or "There's obviously pluses and minuses to it."…”
Section: Research Question 1: How Do People Who Radically Acceleratedmentioning
confidence: 63%
“…Other Benefits of EC Participation Furthermore, ECs have positive effects on students' development of soft skills essential for college success. McDonald and Farrell (2012) found that students credited their EC participation for enhancing their time-management skills, increasing their confidence in navigating the college environment, and affirming their college student identity. Duncheon (2020) reported EC students felt their participation in dual credit prepared them for college by strengthening their test-taking skills, allowing them to form student-professor relationships, and exposing them to the increased freedom and autonomy associated with college.…”
Section: Postsecondary Benefitsmentioning
confidence: 99%
“…Tensions between the two became apparent as EC students juxtaposed the freedom, trust, and autonomy they experienced in their college courses with the strict codes of conduct and rules at their high schools. Similarly, McDonald and Farrell (2012) outlined a push-and-pull effect as students balanced their former high school identities and their newly formed college identity. Students reported needing to adapt their behavior and mentality as they straddled two developmental stages.…”
Section: Concernsmentioning
confidence: 99%
“…Similarly, in a qualitative case study on 21 students' experiences during the first 3 years of an ECHS, Ongaga (2010) found that while caring relationships supported their success, some students reported struggling with time management, newly rigorous academics, and a relative lack of extracurricular activities. McDonald and Farrell (2012) found that students were initially concerned about transitioning into college but that specific college readiness, social, and personal identity concerns were addressed by the ECHS. In Alaie's (2011) case study of ECHS students' initial experiences attending a college course, students found they lacked the study strategies to be successful on long-term assignments and struggled with adapting to the greater responsibilities and increased workload.…”
Section: Challenges Experienced At Echssmentioning
confidence: 99%